PERISTALTIC TRASPORTATION WITH EFFECT OF MAGNETIC FIELD IN A FLEXIBLE CHANNEL UNDER AN OSCILATORY FLUX - kumar, Dr.S.Ravi (Journal of Global Research in Mathematical Archives(JGRMA), 2013)
In this paper we have analyzed the flow of a couple stress fluids in a channel bounded by flexible walls over which a traveling wave of contraction and expansion is imposed resulting in a peristaltic motion. An oscillatory time dependent flow is also imposed on this flow. The non-linear equations governing the flow through magnetic field are solved under long wavelength approximation. The existence of separation in the flow field is discussed for different values of the governing parameters. The behavior of the primary and secondary velocity components, the shear stresses on the wall, the time average fluxes have been analyzed in either case for different sets of parameters.